PENGARUH PEMASARAN PRODUK BEAUTY CARE L'OREAL GROUP TERHADAP PRODUK BEAUTY CARE LOCAL DI INDONESIA TAHUN 2010-2020 - Marisa Devitri; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study examines the effect of marketing l'oreal and local products to compete with other cosmetic brands in Indonesia. Multinational Coorperation or MNC is a form of cooperation that is engaged in various fields of production and range of operations across market borders. L'oreal is one of the multinational collaborations that is growing rapidly in this research. This research is theoretically built using the theories and concepts of multinational cooperation. Researchers formulate all data from books, journals, encyclopedias, media, and websites. The theoretical framework in this study uses qualitative methods. This research proves that PT. L'oreal Indonesia has several ways so that its cosmetic products can compete with other cosmetic brands in Indonesia in 2010-2020.Keywords: Business competition, Multinational companies, market country boundaries, Multinational cooperation concept.